Plasma functionalization of carbon nanotubes and radical penetration mechanism. Issue 8 (25th April 2022) - Jung, Unseok; Kim, Hyun Su; Jeong, Hyeon Su; Suhr, Jonghwan; Kim, Tae‐Hwan; Lee, Hunsu
Abstract: Owing to their superior properties, carbon nanotubes (CNTs) have attracted significant attention for various applications; however, their aggregation due to van der Waals forces hinders the industrial applications of CNTs. To overcome this problem, previous studies have proposed plasma functionalization, but its analysis is limited to the surface of thin‐film materials or involved small quantities of CNTs. In plasma functionalization, radicals need to penetrate from plasma into the CNTs to functionalize the entire CNTs. The radical penetration at all depths of CNTs is experimentally confirmed. The radical penetration mechanism with respect to thickness and free volume between CNTs is modeled using radical diffusion motion with the adoption of Knudsen diffusion. Abstract : In plasma functionalization, it is confirmed that radicals penetrate from plasma into the deepest layer of carbon nanotubes (CNTs) to functionalize the entirety of CNTs. When the thickness of CNTs increases, the radical penetration is hindered, which leads to an increase in treatment time for plasma functionalization. However, when the porosity increases, the thickness effect is offset, which leads to a shortened treatment time. These experimental results are consistent with the calculated results by the radical penetration model.